Neonatal Circumcision Trends from a Pediatric Urology Perspective: Results from a Survey of Members of the Societies for Pediatric Urology. Issue 5 (29th September 2021) - Kraft, Heather; Colon-Sanchez, Kaity; Ellsworth, Pamela
Abstract: Introduction: Neonatal circumcision remains controversial, with rates varying over the years. The Centers for Disease Control and Prevention and the American Academy of Pediatrics acknowledge the health benefits of neonatal circumcision and support access to the procedure for families who choose it. Although more commonly performed by nonurological providers, pediatric urologists are often involved with pre-procedural or post-procedural concerns. Neonatal circumcision trends and perspectives were evaluated as determined by members of the Societies for Pediatric Urology nationwide. Methods: A 20-question survey was distributed electronically via SurveyMonkey to members of the Societies for Pediatric Urology. The survey was developed to assess pediatric urologists' roles in and criteria for neonatal circumcision as well as attitudes towards nonurological provider circumcisions. Of the 20 questions 16 formed the basis of this study. Four questions evaluated "perceptions" and were excluded from study analysis due to subjectivity. Results: Of the surveys 223 (37.2%) were returned. Most responders (80.1%, 177) perform neonatal circumcision. Significant differences exist across geographical regions nationally including common practices, techniques, and financial coverage of neonatal circumcision. However, 70.6% of responders noted a maximum age at time of circumcision of 12 weeks or younger and 48.9% noted a maximum weight of 12 pounds (5.44 kilograms) or less. Conclusions: This study assessed pediatric urologists' roles in and criteria for neonatal circumcision. The development of universal best practices as determined by pediatric urologists, as experts in the field, may prove beneficial for optimizing patient care and nonurological circumcision provider education and training.